Analisa kepuasan pelanggan Original Equipment Manufacturing ban motor dengan metode IPA-QFD: Studi kasus di PT. GTB - Johan Saputra (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
PT. GTB is a manufacturing company that manufactures tyres for motor vehicles, one of them motorcycle tires. The market segmentation of PT. GTB is an Original Equipment Manufacturing (OEM) market. Based on OEM market segmentation, PT. GTB has two large customer groups that include OEM customers.  The complaint level of the customer for the use of motor tires in 2017 as much as 622 times and year 2018 as much as 352 times.  In an effort to maintain the sustainability of product sales, customer complaints are critical to the company's improvement focus. The purpose of this research is analyzing the types of customers complain the use of motor tires. In the early stages, interviews as a reference for conducting customer satisfaction surveys are further analyzed by the Importance Performance Analysis (IPA) and Quality Function Deployment (QFD) methods.  Based on the results of this research, known customer satisfaction rate of the use of GTB motor tires on average is 3.56 which is lower than the customer's expectation of 4.40. The research has successfully identified seven priority attributes that are considered very important to the customer, which is the input for the company to do the improvement.